Job evaluation and an application - Mutlu, Sevda (My University, 2001)
Iş değerlemesi, bir işyerinde mevcut işler arasındaki değer farklılıklarını ortaya çıkaran sistematik bir yöntemdir. Iş değerlemesi ile işlerin zorluk dereceleri ve işyeri için önemleri analiz edilerek gerçekçi ve düzenli bir iş hiyerarşisi oluşturulur. Bu tezin amacı, bir işyerinde orta kademe yöneticilik için bir iş değerleme uygulaması yapmaktır. Bunun için, beyaz eşya endüstrisi sektöründe faaliyet gösteren bir şirkette orta kademe yönetimi dahilinde bütün işler örneklem oalrak seçilmiştir. Söz konusu işlerin araştırmacı tarafından geliştirilen bir anket formu ile analiz edilerek iş tanımlarının ve iş gereklerinin hazırlanması hedeflenmiştir. Iş değelemesi yöntemleri arasından puan faktör yöntemi seçilmiş ve çalışmanın başında tespit edilen ve tanımlanan işi oluşturan faktörlere puan değerlerinin verilmesi ile işlerin toplam puan değerleri bulunmuştur. Bu çalışmanın asıl konusu, şirket kültürü ve değerleri doğrultusunda yönetsel nitelikli işler için bir iş analizi anket formu oluşturmak ve iş değerleme planı geliştirip uygulamaktır. Hazırlanan anket formu ile seçilen iş grubunun iş analizleri ve değerlemesi yapılmış ve göreceli değer farklılıkları ortaya çıkarılmıştır.

Job evaluation is a systenetic process of assessing the value of each job in relation to other jobs within an organization. It is intended to provide a rational, orderly hierarchy of jobs based on their worth to the company by analyzing the difficulty of the work performed and the importance of the work to the organization. The purpose of this MA thesis is to carry out a job evaluation application for managerial positions in an organization. To serve this aim, all middle - level managerial jobs of an organization operating in the field of durable goods industry were taken as a sample. These jobs have been analyzed by using questionnaire form developed by the researcher and next, job descriptions and job specifications have been prepared. From amongst the job evaluation methods, point factor ratingmethod has been chosen. By giving point values to previously selected and defined factors forming the job, total point values of jobs under study have been found out. The design of a job analysis questionnaire form and the deveolopment and implementation of a job evaluation plan for managerial positions according to the organizational culture and values is the subject of this MA thesis. A job analysis has been carried out by means of prepared questionnaire, evaluation of selected jobs has been realized, and comparable worth of these jobs have been found out.
Keywords: Ekonomi; Emek ekonomisi; Insan Kaynakları; Iş Değerleme; İşgücü pazarı